A utility theory of `truth' - Arthur, Alex (2003)
Some important philosophical issues to do with trust, meaning and translation are raised if we attempt to take the language of business seriously. There may be difficulties associated with trying to make sense of what this would amount to, but a preliminary exploration of the territory provides interesting perspectives on business ethics and on the philosophy of language. When we decide that we know what another speaker is saying, we are simultaneously making decisions about the way the world is, the structure of the speaker's language and the speaker's veracity. Since there is an irreducible ethical dimension to translation, a decision to `translate' business language as ethical, but simply having different t ruth values, is not going to be `right' or `wrong' except in the context of an ethical stance taken by the translator. In other words, it is no different from a decision to adjust one's ethical position into conformity with the values apparently embedded in business practice. - Reproduced.
Keywords: Enterprises; Business Ethics